Testing Scheme Design for Grabbing Positioning and Release Mechanism in Space Microgravity Environment - Yang Zhong; Huisen Zhang; Chao Xue (Sensors)
In the context of a space-based gravitational wave detection mission, the grabbing positioning and release mechanism (GPRM) is tasked with ensuring that the test mass (TM) is securely fixed in the appropriate configuration at the time of the satellite launch and subsequently releasing the TM in orbit at extremely low speeds across three translational and three rotational degrees of freedom. Consequently, the assessment of the GPRM functionality in a microgravity environment is a crucial step in the advancement of gravitational wave detection technology. In this paper, we present a space testing scheme for measuring the full six degrees of freedom of the test mass following its release. This was achieved through the use of a sensing system that employed spectral confocal displacement sensors and was equipped with a vacuum system, which enabled the simulation of a vacuum environment similar to that experienced in orbit. The accuracy of the testing scheme was validated by a Monte Carlo simulation test, which demonstrated that it could achieve 5 <semantics>μ</semantics>m and 82 <semantics>μ</semantics>rad in translational and rotational displacement measurement, respectively, and the translational and rotational velocities were found to be 0.08 <semantics>μ</semantics>m/s and 1.4 <semantics>μ</semantics>rad/s, respectively, over a four-second test time.